Aspectos bionômicos de Geometridae (Lepidoptera) associados à Rapanea umbellata (Mart.) Mez, 1902 (Myrsinaceae) na Região de São Carlos, SP - Barros, Luciana Tereza Estriga de (2007)
This work was carried out in three different areas of Universidade Federal de São Carlos. We studied the Geometridae associated to Rapanea umbellata (Mart.) Mez, 1902 (Myrsinaceae). The samples were collected at each two weeks, during the period of October of 2005 to april of 2007. It was used the method of entomological umbrella. The larvae were grown in the laboratory, using the host plant as food. Rapanea umbellata had the first register as plant hostess of Geometridae in the present study. It occured 14 species of Geometridae arranged in 11 genus, seven genus of Hymenoptera Parasitica and one Diptera. The common species that occured was Phrygionis polita (Cramer, 1780), whose relative abundance was 48,9%. Other Geometridae recordered were: P. paradoxata (Guenée, [1858]), Argyrotome melae (Druce, 1892), Opisthoxia sp. Hübner, [1825], Pero refellaria (Guenée, [1858]), Glena bipennaria (Guenée, [1858]), G. unipennaria (Guenée, [1858]), Hymenomima amberia (Schaus, 1901), Iridopsis chalcea (Obertür, 1883), Ischnopteris miseliata (Guenée, [1858]), Patalene Herrich-Schäffer, [1854], Oxydia apidania (Cramer, [1779]), O. vesulia (Cramer, [1779]), Prochoerodes tetragonata (Guenée, [1958]). The Hymenoptera parasitoids were: Euplectrus Nestwood, 1832 (Eulophidae), Charops Homgren, 1859 (Ichneumonidae), Hyposoter Foerster, 1869 (Ichneumonidae), Mesochorus Gravenhorst, 1829 (Ichneumonidae), Diolcogaster Asmed, 1900 (Braconidae), Hymenochaonia Dalla Torre, 1898 (Braconidae), Glyptapanteles Ashmed, 1905 (Braconidae). The density of larvae shows two peaks, one at the dry season and one at the raining season. In the same time occurs the smaller percentage of parasitism. The cycle of development of Phrygionis polita was studied, being the first description of the immature stages of a species of the Palyadini tribe.